Electron driven mobility model by light on the stacked metal–dielectric interfaces. Issue 7 (16th May 2017) - Pornsuwancharoen, N.; Youplao, Pichai; Amiri, I.S.; Ali, Jalil; Yupapin, Preecha
Abstract: An electron mobility enhancement is the very important phenomenon of an electron in the electronic device, where the high electronic device performance has the good electron mobility, which is obtained by the overall electron drift velocity in the electronic material driven potential difference. The increase in electron mobility by the injected high group velocity pulse is proposed in this article. By using light pulse input into the nonlinear microring resonator, light pulse group velocity can be tuned and increased, from which the required output group velocity can be obtained, which can be used to drive electron within the plasmonic waveguide, where eventually, the relative electron mobility can be obtained, the increasing in the electron mobility after adding up by the driven optical fields can be connected to the external electronic devices and circuits, which can be useful for many applications.